PENGARUH PERLAKUAN BENIH DENGAN AGENS HAYATI TERHADAP PERTUMBUHAN, HASIL PADI, DAN PENGENDALIAN PENYAKIT HAWAR DAUN BAKTERI DI RUMAH KACA - Agustiansyah, Agustiansyah; Ilyas, Satriyas; Sudarsono, Sudarsono; Machmud, Muhammad (JURNAL AGROTROPIKA, 2011)
The objective of this research was to study the influence of biological seed treatment on plant growth, yield of rice, and controlling of bacterial leaf blight. The research was conducted at green house of Indonesian Center for Agricultural Biotechnology and Genetic Resources Development, Bogor and Seed Science and Technology Laboratory, Department of Agronomy IPB from August 2009 to Febru-ary 2010. The result showed that biological seed treatment of Pseudomonas spp. and Bacillus spp. (with and without matriconditioning) could increase plant growth of rice in terms of on plant height, number of seedling, root length, root fresh weight, root dry weight, shoot fresh weight, and shoot dry weight. Seed treatments of matriconditioning + P.aeruginosa, matriconditioning + B.subtillis5/B, and Bacillus subtillis 11/C were the best seed treatments in increasing yield of rice as indicated by the highest number of filled grains/panicle, percentage of filled grain/panicle, percentage of filled grain/plant, and the lowest number of unfilled grain/panicle, percentage of unfilled grain/panicle, and percentage unfilled grain/plant. Seed treatments of Pseudomonas diminuta, matriconditioning + Pseudomonas diminuta and matriconditioning + Bacillus subtilis 11/C were significantly resulted in lower percentage of pathogen diseased leaf area (%DLA) than others seed treatment. Percentages of pathogen diseased leaf area were 15.45%, 15.94% and 19.55%. Key words: Bacillus spp Biological seed treatment, matriconditioning, Pseudomonas spp.